Efficient Monitoring of Treatment Response during Youth Psychotherapy: The Behavior and Feelings Survey - Weisz, John R.; Vaughn-Coaxum, Rachel A.; Evans, Spencer C.; Thomassin, Kristel; Hersh, Jacqueline; Ng, Mei Yi; Lau, Nancy; Lee, Erica H.; Raftery-Helmer, Jacquelyn N.; Mair, Patrick (Journal of clinical child and adolescent psychology, 2020)
An emerging trend in youth psychotherapy is measurement-based care (MBC): treatment guided by frequent measurement of client response, with ongoing feedback to the treating clinician. MBC is especially needed for treatment that addresses internalizing and externalizing problems, which are common among treatment-seeking youths. A very brief measure is needed, for frequent administration, generating both youth- and caregiver-reports, meeting psychometric standards, and available at no cost. We developed such a measure to monitor youth response during psychotherapy for internalizing and externalizing problems. Across 4 studies, we used ethnically diverse, clinically relevant samples of caregivers and youths ages 7-15 to develop and test the Behavior and Feelings Survey (BFS). In Study 1, candidate items identified by outpatient youths and their caregivers were examined via an MTurk survey, with item response theory methods used to eliminate misfitting items. Studies 2-4 used separate clinical samples of youths and their caregivers to finalize the 12-item BFS (6 internalizing and 6 externalizing items), examine its psychometric properties, and assess its performance in monitoring progress during psychotherapy. The BFS showed robust factor structure, internal consistency, test-retest reliability, convergent and discriminant validity in relation to three well-established symptom measures, and slopes of change indicating efficacy in monitoring treatment progress during therapy. The BFS is a brief, free youth- and caregiver-report measure of internalizing and externalizing problems, with psychometric evidence supporting its use for MBC in clinical and research contexts.